PECHA KUCHA : A WAY TO DEVELOP PRESENTATION SKILL - Lulut Widyaningrum (Vision: Journal for Language and Foreign Language Learning, 2016)
This study is aimed at applying the adaptive Pecha Kucha technique to find out its effectiveness on students’ explaining skill, one of the skills that should be mastered among ELT Department students. This study uses a Quasi-experimental with Randomized Control Group Pretest-Posttest. The two groups (experimental and control group) selected will be ob- served in which the experimental group is going to be taught how to use adaptive Pecha Kucha, while the control group will be asked to explore the traditional model of PPT presentation. The data are gained through ob- servation, questionnaire, and comprehension test. The results show that the adaptive Pecha Kucha technique can develop students’ explaining skill, performance and comprehension. With a good preparation and clear per- formance rule, the technique shows to be more effective than the com- mon Power Point presentation. The data analysis of students comprehen- sion shows that the t-statistics was 6.44, while the value of t-table with the significance level of 5% and the Df (Degree of Freedom) 18 was 1. 734. It could be said that the t-statistics is higher than t-table. It also proved that the hypothesis which say there is significant different of exploring adaptive Pecha Kucha technique than students’ Power Point presentation is accepted. It showed that adaptive Pecha Kucha is really effective to do the presentation. Though, the students need more time and preparation, this technique is badly employed due to its effectiveness and to support the pre-service teachers’ development.